The The Right to Life Based on The International Covenant on Civil And Political Rights And Its Application In Indonesian National Law - Abdul Kadir Zaylani Muhtar; Muh. Risnain; Zunnuraeni (Department of Law, Faculty of Law, University of Mataram, 2024)
This study aims to analyze and understand the protection of the right to life under the International Covenant on Civil and Political Rights (ICCPR) and its application in Indonesia. It also seeks to evaluate whether its implementation in Indonesian national law, particularly concerning terrorism, narcotics, and corruption crimes, aligns with the mandates of the ICCPR. The research methodology used is normative legal research. The findings indicate that the right to life as regulated by the ICCPR and its implementation in Indonesia are consistent and non-contradictory, including the application of the death penalty for terrorism, narcotics, and corruption crimes. This is because the ICCPR restricts the death penalty to the most serious crimes, and these three crimes fall into that category.